The MINOS calibration detector - Adamson, P; Crone, G; Jenner, L; Nichol, R; Saakyan, R; Smith, C; Thomas, J; Kordosky, M; Lang, K; Vahle, P; Belias, A; Nicholls, T; et al. (2006)
This paper describes the MINOS calibration detector (CalDet) and the procedure used to calibrate it. The CalDet, a scaled-down but functionally equivalent model of the MINOS Far and Near detectors, was exposed to test beams in the CERN PS East Area during 2001-2003 to establish the response of the MINOS calorimeters to hadrons, electrons and muons in the range 0.2-10 GeV/c. The CalDet measurements are used to fix the energy scale and constrain Monte Carlo simulations of MINOS. © 2005 Elsevier B.V. All rights reserved.